2007
DOI: 10.1017/s0014479706004558
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTIVE FLOWERING TIME VARIATIONS IN UPLAND COTTON (GOSSYPIUM HIRSUTUM) AT DIFFERENT PLANTING DATES AND STAND DENSITIES IN BENIN

Abstract: Effective flowering time in Gossypium hirsutum cotton plants was studied with the aim of enhancing decision making on the best varieties to plant according to the planting date under rainfed cropping conditions. Trials were conducted at two sites in a cotton-growing area of Benin in 2002 and 2003. A split-split plot design with three replicates was used to compare 10 cotton varieties, with different growth cycle lengths and morphology, at three stand densities (42 000, 125 000, 167 000 plants ha −1 ) and two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
0
6
0
2
Order By: Relevance
“…This deficit was offset under late planting-high stand density conditions, but yields, except for Mar 88-214, still did not surpass those of later varieties with less determinate growth, thus confirming previous results obtained by Crawley et al (2004), Galanopoulou-Sendouka et al (1980) and Porter et al (1995). In late planting conditions, the effective flowering time is uniformly shorter for all ideotypes (Sekloka et al, 2007b) and early varieties do not fully benefit from their higher yielding capacity. In North Carolina, May and Bridges (1995) also found no significant genotype by late or early cropping system interaction for yield, but their results were obtained with a narrow genetic pool of lines already adapted to intensive agriculture (irrigation, mechanical harvest).…”
Section: Discussion a N D B R E E D I N G S T R At E G I E Smentioning
confidence: 95%
See 2 more Smart Citations
“…This deficit was offset under late planting-high stand density conditions, but yields, except for Mar 88-214, still did not surpass those of later varieties with less determinate growth, thus confirming previous results obtained by Crawley et al (2004), Galanopoulou-Sendouka et al (1980) and Porter et al (1995). In late planting conditions, the effective flowering time is uniformly shorter for all ideotypes (Sekloka et al, 2007b) and early varieties do not fully benefit from their higher yielding capacity. In North Carolina, May and Bridges (1995) also found no significant genotype by late or early cropping system interaction for yield, but their results were obtained with a narrow genetic pool of lines already adapted to intensive agriculture (irrigation, mechanical harvest).…”
Section: Discussion a N D B R E E D I N G S T R At E G I E Smentioning
confidence: 95%
“…(1995). In late planting conditions, the effective flowering time is uniformly shorter for all ideotypes (Sekloka et al ., 2007b) and early varieties do not fully benefit from their higher yielding capacity. In North Carolina, May and Bridges (1995) also found no significant genotype by late or early cropping system interaction for yield, but their results were obtained with a narrow genetic pool of lines already adapted to intensive agriculture (irrigation, mechanical harvest).…”
Section: Discussion and Breeding Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Jost and Cothren (2000) reported earlier maturity in UNRC than in CONC, which was thought to result from CONC producing more main stem nodes than UNRC. Sekloka et al (2007) also reported that effective flowering time can be effected by varieties with relatively longer growth cycles.…”
Section: Resultsmentioning
confidence: 95%
“…Concerning effective flowering date, the UNRC produced flowers earlier at NAWF 1, 2, 3, 4, and 5 (84, 80, 75, 72, and 70 d after planting) compared with the CONC (88, 85, 80, 76, and 72 d). Sekloka et al (2007) also indicated that higher plant densities slightly reduce effective flowering dates. Moreover, Jost and Cothren (2000) reported earlier maturity in UNRC than in CONC, which was thought to result from CONC producing more main stem nodes than UNRC.…”
Section: Resultsmentioning
confidence: 96%